FAKTOR-FAKTOR YANG MEMPENGARUHI TINGGINYA LAJU PERTUMBUHAN DAN IMPLEMENTASI KEBIJAKAN PENDUDUK DI PROVINSI BALI - I Nyoman, Suartha (PIRAMIDA; Vol 12 No 1 (2016), 2016)
High rate of population growth causes population problems to be huge problems that should be solved; if don’t’ there will be “Population Bomb”( Paul R. Ehrlich,1968). Factors affecting the rate of population growth after conducting analysis with quantitative and qualitative descriptive research approach and statistical analysis and public regulation theory by Edward III; in which the research object is in all Regencies/City in Bali. The rate of population growth determined by the change of population dynamics as well as: fertility, mortality, and migration in Bali Province. The rate of population growth is much higher than the national rate of population growth. Although the acquired bonus demography, in which Total Fertility Rate (TFR) has been decreasing from 2,5 to be 2,3 per women however the Mortality Rate is still above one percent and migration rate level in the area of Sarbagita is very high even reaches more than 4 percent. The effort of controlling the population through Keluarga Berencana (Family Planning) is still stagnant, as the consequences of the weakness of the government regulation implementation.
Keywords: Population Growth, Demographic Dividend, Implementation of Public Regulation